2017
DOI: 10.5114/wo.2017.72393
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the long-term outcomes of sorafenib therapy in routine practice in imatinib and sunitinib resistant gastrointestinal stromal tumors (GIST)*

Abstract: Aim of the studywas to analyze the outcome of treatment and factors predicting results of sorafenib therapy in inoperable/metastatic CD117-positive GIST patients after failure on imatinib and sunitinib.Material and methodsWe identified 60 consecutive patients (40 men, 20 women) with advanced inoperable/metastatic GIST after failure on at least imatinib and sunitinib treated in one sarcoma center with sorafenib at initial dose 2 × 400 mg daily in 2007–2015 (in 56 cases it was 3rd line therapy). Median follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…There have been several retrospective studies that have evaluated the efficacy of sorafenib therapy in third-line and fourth-line treatment of advanced GIST. The median PFS and OS were shown to be 7.2 months and 15.2 months, respectively in a study that included 25 patients [14], 20 weeks and 42 weeks, respectively in a study that included 32 patients undergoing fourth-line treatment after nilotinib [15], 7.7 months and 13.5 months, respectively in a study that included 60 patients [16] and 6.4 months and 13.5 months, respectively in a study that included 124 patients [17]. In some studies, a significantly increased PFS was found in patients with improved performance status [17].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several retrospective studies that have evaluated the efficacy of sorafenib therapy in third-line and fourth-line treatment of advanced GIST. The median PFS and OS were shown to be 7.2 months and 15.2 months, respectively in a study that included 25 patients [14], 20 weeks and 42 weeks, respectively in a study that included 32 patients undergoing fourth-line treatment after nilotinib [15], 7.7 months and 13.5 months, respectively in a study that included 60 patients [16] and 6.4 months and 13.5 months, respectively in a study that included 124 patients [17]. In some studies, a significantly increased PFS was found in patients with improved performance status [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study the median PFS was 27 weeks in sunitinib group in comparison to 6 weeks in the placebo group [17][18][19]. In case of further progression or sunitinib intolerance, regorafenib and sorafenib are subsequent therapeutic options, although sorafenib is not approved for GIST treatment [20,21]. Regorafenib, another multikinase inhibitor targeting KIT, PDGFR, VEGFR, FGFR (fibroblast growth factor receptor) and RET, was registered in third-line treatment based on a phase III study named GRID (NCT01271712).…”
Section: Treatmentmentioning
confidence: 99%
“…The most important adverse events during regorafenib treatment included hypertension, hand-foot syndrome, and diarrhoea. In Poland, it is now possible to treat patients after progression during imatinib and sunitinib therapy with sorafenib in addition to registration indications (off label) under the drug program based on the positive results of the phase II study and cohort studies [28,29]. In the case of further progression, it is recommended that the patient be included in clinical trials with new drugs (e.g.…”
Section: Treatment Of Advanced Stagementioning
confidence: 99%